THE EFFECT OF ASEAN CG SCORECARD ON COMPANY VALUE WITH SUSTAINABILITY REPORT AS AN INTERVENING VARIABLES - Gilbert Rely (JOEL: Journal of Educational and Language Research, 2022)
The purpose of this study was to examine the effect of the ASEAN CG Scorecard on corporate value and sustainability report as an intervening variable. companies listed on the Indonesia Stock Exchange during the period 2014-2017. The research sample was selected using the purposive sampling method. The research analysis used multiple linear regression test with the help of SPSS 20.0 software. The results of the study showed that there were 16 companies that met the population target set in the study. Based on the results of multiple linear analysis with a significance level of 5%, the results of this study conclude that Good corporate governance does not have a positive effect on the sustainability report. Good corporate governance has a positive effect on company value. Sustainability report cannot mediate the positive influence of good corporate governance on company value.